An Analytical Study on Factors Influencing Financial Performance of Selected Private Sector Banks in India during Precovid, Covid and Post Covid Period - D.Kasthuri; Dr. S.Saratha (International Journal of Engineering and Management Research, 2024)
This study focuses on the financial performance of banks, emphasizing key aspects such as profitability, efficiency, asset quality, and market valuation. Profitability measures how effectively banks generate income in relation to their assets and expenses, which is crucial for sustainability. Efficiency metrics, such as operating cost ratios, indicate how well a bank manages its expenses relative to its income, directly impacting profitability. Asset quality, often evaluated by non-performing assets, plays a significant role in financial health, as poor asset quality can lead to higher risks. Liquidity management ensures that banks can meet their financial obligations, while market valuation reflects investor perception and future expectations. A balanced focus on these factors provides a clear picture of a bank's financial stability, growth potential, and resilience in a competitive financial environment.